Morgan’s Legacy: Fruit Flies and the Functional Annotation of Conserved Genes - Bellen, Hugo J. (Cell, 2015)
In 1915, “The Mechanism of Mendelian Heredity” was published by four prominent Drosophila geneticists. They discovered that genes form linkage groups on chromosomes inherited in a Mendelian fashion and laid the genetic foundation that promoted Drosophila as a model organism. Flies continue to offer great opportunities, including studies in the field of functional genomics.